Screening for cognitive impairment among patients with work-related stress complaints in Denmark: validation and evaluation of objective and self-report tools - Jensen, Johan Høy; Miskowiak, Kamilla Woznica; Purdon, Scot E.; Thomsen, Jane Frølund; Eller, Nanna Hurwitz (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVE ': 'Many patients with work-related stress display cognitive impairment that may hamper recovery. We examined objective and subjective tools for screening of cognitive impairment in this patient group. ' ' METHODS ': 'Patients were assessed with Danish versions of the objective Screen for Cognitive Impairment in Psychiatry (SCIP-D), standardized neuropsychological tests that tapped into the same cognitive domains, the self-assessed Cognitive Failure Questionnaire (CFQ), and several additional scales of symptom severity and psychosocial status. Concurrent validity of the SCIP-D and CFQ was assessed by calculation of Pearson’s correlation coefficients between the objective and subjective tools and the scores on more conventional standardized neuropsychological tests. Decision validity was assessed with logistic receiver-operating-characteristic analyses using a cut-score approach to the objective and the subjective test results to predict impairment detected by the standardized tests. Cognitive norms were established through the data of 79 healthy controls. SCIP-D scores were compared between patients and healthy controls with independent t-tests. ' ' RESULTS ': 'We included 82 patients with work-related stress. The SCIP-D total scores were strongly associated with standardized neuropsychological tests (r=0.76, P<0.001). The self-assessed CFQ was not associated with either measure of objective cognitive functioning (r≤0.12, P≥0.30). The optimal SCIP-D total-score cut of ≤72 identified 43.2% of the patients with global objective cognitive impairment. The patients performed mildly-to.moderately lower than the healthy controls on the SCIP-D total score (Cohen’s d=0.39) and the subtests for working memory (d=0.39) and processing speed (d=0.61). ' ' CONCLUSION ': 'The SCIP-D is a valid screening tool sensitive to objective performance-based cognitive impairment among patients with work-related stress.
Keywords: assessment; attention; burnout; cognitive impairment; Denmark; evaluation; exhaustion disorder; memory; neuropsychological test; SCIP; self-rated health; self-report; stress; validation; work-related stress; working memory